True random number generation using CMOS Boolean chaotic oscillator. Issue 12 (December 2015) - Park, Myunghwan; Rodgers, John C.; Lathrop, Daniel P.
Abstract: We report on a random number generator whose randomness derives from a Boolean chaotic oscillator, designed and fabricated as an integrated circuit. The underlying physics of chaotic dynamics in the Boolean chaotic oscillator is verified by time domain analysis, frequency domain analysis, and computation of Lyapunov exponents. To test the hypothesis physically, a discrete Boolean chaotic oscillator is implemented using commercial chips on printed circuit boards. Using a CMOS 0.35 μm process, we build a CMOS Boolean chaotic oscillator, which consists of a core chaotic oscillator and a source follower buffer. The quality of the measured bit sequences makes a suitable randomness source, and its property is analyzed using NIST standard statistical tests after subsequent post-processings. This circuit requires 0.087 nJ for a generation of single random bit with the chip area of 0.057 mm 2 .